Transforming gesture to sign in the theatre - Lutterbie, John (TECCOGS: Revista Digital de Tecnologias Cognitivas, 2021)
This paper explores the transition from speech-gesture to theatrical gesture. Gestures, according to David McNeill and Susan Goldin-Meadow, are an integral part of speech, performing a crucial function in the organization of thought into language. In acting gesture is defined as a sign that communicates a character‟s action, state of mind and relationship with other characters to an audience. Portraying Granpa Joad, in a production of The Grapes of Wrath, I performed a spontaneous gesture in rehearsal that, fulfilling the needs of a theatrical gesture, was transformed into a sign through the repetition of rehearsal. Dynamic Systems Theory is used to understand the transformative process of making a spontaneous gesture into a complex, intentional, and communicative act. Key Words: Dynamic Systems Theory, Gesture, Language, Signs, Acting, Theatre